Absenteeism of Doctors in Public Healthcare Facilities in a District of Bangladesh (Sir Salimullah Medical College Journal, 2026)
Background: Absenteeism of doctors in health care facilities is a critical challenge. Poor retention of doctors in government healthcare facilities remains underexplored. Objective: The research aimed to explore reasons behind absenteeism of doctors in workplace and perceived mitigation measures. Methods: The cross sectional study extended from July 2024 to June 2025. A sample of 195 doctors were purposively selected from 1medical college, 1 district hospital and 7 upazilla health complexes in Noakhali district. Data were collected through face to face interview using pretested semi structured questionnaire. Ethical clearance from Institutional Review Board of Sir Salimullah Medical College and informed consent from participants were taken. Chi square test and logistic regression were done using the SPSS version 26. Results: Frequency of absenteeism among doctors was 22.6%. Logistic regression identified being male (OR=6.93, p=0.008) and having poor toilet facility (OR=32.30, p=0.003) increased absenteeism, while spouse working in same area (OR=0.023, p=0.005), safe workplace (OR=0.00, p=0.003), and presence of designated security guard (OR=0.345, p=0.034) reduced absenteeism. Conclusion: Conducive workplace ensuring workplace safety and family support, would contribute in mitigation of doctor’s absenteeism in government health facilities. Strengthening the health system through infrastructure development, recruiting health workers, and building necessary support systems will improve efficiency in health system.Sir Salimullah Med Coll J 2025; 33: 99-106